TIPOLOGI JAMINAN: PERSPEKTIF KOMPILASI HUKUM EKONOMI SYARIAH DAN JAMINAN KEPERDATAAN - Adityo, Rayno Dwi (Jurnal Yuridis, 2015)
The development of the world of business law particularly in the field of economic demands the availability of islamic law that will be a legal framework to guarantee certainty and justice. The increasing of this case is seen from growing number of banks and financial institution sector non bank using syariah principle and one of the legal instruments needed is the collateral. Collateral aspect was in a Compilation of Sharia Economic Law (KHES) and there is also warranty aspect in private law. In fact, KHES collateral aspect is not explained holisticly and led to the absence of significant differences of collateral in general including its legal consequenses. There is one of the equation on the term ?kafalah bi an-nafs? at KHES same as collateral person in private law and also the term ?kafalah bi al-mal? same as with collateral material in privatelaw.